The possible influence of the COVID-19 pandemic on the fluctuation in the number of HPV infection cases in Brazil (Research, Society and Development, 2024)
The article aims to highlight the influence of the COVID-19 pandemic on the fluctuation of HPV infection cases in Brazil. Emphasizing the pandemic as a global challenge, it underscores the spread of SARS-CoV-2 and its impact on public health. It relates the pandemic to the decline in vaccination campaigns, including the HPV vaccine. Qualitative and quantitative examination of documents related to the subject was sought, collected from secondary sources such as Pubmed, Scientific Electronic Library Online (SciELO), and DATASUS. The results indicate the impacts of COVID-19, highlighting the lack of coordination in the Brazilian response, the interruption of routine medical services, and the decrease in vaccination rates. The work emphasizes that HPV experienced a decline in vaccine coverage between 2019 and 2022. It can be concluded that there was a significant repercussion of the health crisis on immunization strategies, demonstrating a reduction in vaccine coverage and an increase in the anti-vaccine movement. The relationship between the decline in immunization and the increase in HPV infection cases, especially after the pandemic, raises concerns about the possible rise in cervical cancer cases associated with low vaccine coverage.